A comprehensive study on smart cities: recent developments, challenges and opportunities - V. Sandeep; Pallavi V. Honagond; Pooja S. Pujari; Seong-Cheol Kim; Surender Reddy Salkuti (Institute of Advanced Engineering and Science, 2020)
This paper presents the importance and applications of smart cities in view of taxonomy in urbanization particularly in Asia and Africa economies. It describes the characteristics and architecture of smart cites and reviews on the recent technological developments. The paper analyses the social impacts due to up-gradation of existing cities. The implementation goals like policies and standards are still in progressive state. The international organizations like IEEE, ISO, IEC etc are focused in this emerging area and prepared road map for successful deployment of technologies in cities. In this way of development, there are some interesting challenges like visualization, integration, privacy etc, need to be addressed with specific and innovative solutions. The paper highlights the opportunities in developing and governance of smart cities.